2019
DOI: 10.1007/jhep06(2019)081
|View full text |Cite
|
Sign up to set email alerts
|

Meronic Einstein-Yang-Mills black hole in 5D and gravitational spin from isospin effect

Abstract: We construct an analytic black hole solution in SU(2) Einstein-Yang-Mills theory in five dimensions supporting a Meron field. The gauge field is proportional to a pure gauge and has a non-trivial topological charge. The would-be singularity at the Meron core gets shielded from the exterior by the black hole horizon. The metric has only one integration constant, namely, its ADM mass, which is shown to be finite once an appropriate boundary term is added to the action. The thermodynamics is also worked out, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 91 publications
2
33
0
Order By: Relevance
“…There the authors presented the first analytic, self-gravitating Skyrmions with baryon charge 4 in four dimensions and find a novel transition at nonzero baryon charge between embedded and non-embedded gauge field configurations. The topological solution presented in our work bears a resemblance to those constructed in [58]. There the authors work with an Einstein-Yang-Mills model with non-zero cosmological constant and construct a black hole solution with topological charge 1 and discuss its thermodynamics.…”
Section: Jhep03(2021)229mentioning
confidence: 54%
See 1 more Smart Citation
“…There the authors presented the first analytic, self-gravitating Skyrmions with baryon charge 4 in four dimensions and find a novel transition at nonzero baryon charge between embedded and non-embedded gauge field configurations. The topological solution presented in our work bears a resemblance to those constructed in [58]. There the authors work with an Einstein-Yang-Mills model with non-zero cosmological constant and construct a black hole solution with topological charge 1 and discuss its thermodynamics.…”
Section: Jhep03(2021)229mentioning
confidence: 54%
“…As a result of the work of the authors in [52,[56][57][58][59] the authors of [32] have shown that the Einstein-Skyrme theory (2.1) has the same equations of motion as a particular Einstein-Yang-Mills (EYM) theory. The latter contains a massive non-Abelian gauge field with mass m in a pure gauge configuration A µ = λU −1 ∂ µ U , with the SU(2) group element U , and the real-valued parameter λ = 0, 1.…”
Section: Meronsmentioning
confidence: 99%
“…However, on flat spaces, merons cannot be observed directly (as they have infinite Euclidean action/energy). When Yang-Mills theory is coupled with General Relativity (GR), it has been possible to construct analytic examples of merons-black holes [33][34][35][36]. Thus, in a sense, meron-black holes can be observed directly (some peculiar effects have been discussed in [36]), but the meron singularity is still there (although hidden behind the horizon).…”
Section: Introductionmentioning
confidence: 99%
“…When Yang-Mills theory is coupled with General Relativity (GR), it has been possible to construct analytic examples of merons-black holes [33][34][35][36]. Thus, in a sense, meron-black holes can be observed directly (some peculiar effects have been discussed in [36]), but the meron singularity is still there (although hidden behind the horizon). Consequently, the examples in [33][34][35][36] are not gravitating solitons but rather non-Abelian black holes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation